Mars Gravity Field Determination Using Tianwen-1 Orbiter Tracking Data - Chongyang Wang; Jianguo Yan; Shanhong Liu; Shangbiao Sun; Jianfeng Cao; Denggao Qiu; Xie Li; Jean-Pierre Barriot (The Astrophysical Journal Letters)
The Martian gravity field is a key data set for studying the internal structure of Mars. For this purpose, we processed all the two-way Doppler tracking data of the Tianwen-1 orbiter from 2021 June to 2024 October and determined a new degree and order 80 Martian static gravity field model, TW80. The Tianwen-1 orbiter tracking data show high accuracy, with approximately 90% of arcs achieving an rms of residuals of less than 0.1 mm s ^–1 . We evaluated this model in terms of gravity anomaly errors, gravity/topography correlation, and orbit determination performance. The TW80 gravity field model reaches a global resolution of degree and order 74, corresponding to a spatial resolution of approximately 140 km. The rms of the gravity anomaly errors is approximately 35.8 mGal, with notably smaller errors near the south pole region in the southern hemisphere and larger errors in mid- and low-latitude regions. The TW80 model shows a high correlation with topography and is consistent with the MRO120D gravity field model up to degree 40. Due to the highly elliptical orbit geometry, the orbit determination performance of the TW80 model for the Tianwen-1 orbiter is comparable to that of the MRO120D model, with radial differences less than 100 m and total position differences less than 500 m. Further improvements in orbit determination accuracy will focus on precise modeling of orbital maneuvers and the solar radiation pressure model, as well as extending the tracking duration of individual arcs.